2018
DOI: 10.3233/jad-180640
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Alzheimer’s Disease in Obstructive Sleep Apnea Syndrome: Amyloid-β and Tau Imaging

Abstract: Background: An association between obstructive sleep apnea (OSA) and Alzheimer's disease has been suggested but little is known about amyloid-␤ and tau deposition in this syndrome. Objective: To determine amyloid and tau burden and cognitive function in OSA in comparison with those without a diagnosis of OSA. Methods: The status of OSA was determined by asking participants about history of polysomnographic diagnosis of OSA and the use of Continuous Positive Airway Pressure (CPAP). A comprehensive neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Our finding that OSA exacerbates A accumulation in genetically susceptible AD mice is consistent with a previous report that exposure of mice to chronic intermittent hypoxia increases Aβ42 levels in a triple Alzheimer's disease model mouse (Shiota et al, 2013). Similarly, higher brain Aβ (Spira et al, 2014;Elias et al, 2018), or decreased Aβ and increased phosphorylated tau in the cerebrospinal fluid (Osorio et al, 2014b;Osorio et al, 2014a), has been associated with a higher oxygen desaturation in cognitively impaired OSA subjects. One explanation for these observations could be that hypoxia and HIF1α-mediated transcription can directly up-regulate the expression of β-secretase (Zhang et al, 2007), while HIF1α can operate as a regulatory subunit of γ-secretase during hypoxia (Villa et al, 2014), both of which could increase Aβ production via the amyloidogenic pathway.…”
Section: Cbf Degeneration Is An Early Ad Feature That Can Drive Othersupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that OSA exacerbates A accumulation in genetically susceptible AD mice is consistent with a previous report that exposure of mice to chronic intermittent hypoxia increases Aβ42 levels in a triple Alzheimer's disease model mouse (Shiota et al, 2013). Similarly, higher brain Aβ (Spira et al, 2014;Elias et al, 2018), or decreased Aβ and increased phosphorylated tau in the cerebrospinal fluid (Osorio et al, 2014b;Osorio et al, 2014a), has been associated with a higher oxygen desaturation in cognitively impaired OSA subjects. One explanation for these observations could be that hypoxia and HIF1α-mediated transcription can directly up-regulate the expression of β-secretase (Zhang et al, 2007), while HIF1α can operate as a regulatory subunit of γ-secretase during hypoxia (Villa et al, 2014), both of which could increase Aβ production via the amyloidogenic pathway.…”
Section: Cbf Degeneration Is An Early Ad Feature That Can Drive Othersupporting
confidence: 92%
“…Specifically our work highlights intermittent hypoxia as the decisive feature, as it induces cBF neuronal degeneration and cognitive impairment, with a coincident or subsequent increase in the levels of A when linked to a genetic risk for Aβ accumulation (potentially including an ApoE4 genotype; (Yaffe et al, 2014;Wollam et al, 2015)). Although treating the hypoxemia in our OSA model or giving CPAP in humans reduces respiratory disturbance during sleep, and improves working memory, some cognitive aspects such as complex attention and executive function remain impaired (Daulatzai, 2015), daytime sleepiness can continue, and A load can remain unchanged (Elias et al, 2018), all of which might reflect irreversible cBF neuronal loss that predates the commencement of CPAP treatment. Therefore, targeting cholinergic function (through cholinergic esterase inhibition or muscarinic agonists; ), cBF health (through p75NTR modifiers or neurotrophic mimetics; (Longo and Massa, 2013)) or specific HIF1 pathways (2ME2 is a current treatment for tumour angiogenesis) represent candidate treatments for preventing AD in the OSA 'at risk' population -those with intermittent hypoxia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Individuals with vascular dementia, AD and other types of dementia are often diagnosed with sleeping pattern problems. Many studies, which findings are given in Table 6 , have proposed an association between sleep problems, especially, for obstructive sleep apnea patients and a higher risk of dementia [ 56 , 121 , 122 , 123 ]. Some researchers believe that obstructive sleep apnea may even start the AD neuropathological process [ 124 ].…”
Section: Other Established (Non-)modifiable Risk Factors and Possimentioning
confidence: 99%
“…In the past decade, large amounts of work have been devoted to understanding the association between various sleep disturbances (SDs) and AD pathologies. Cross‐sectional studies have suggested that greater amyloid pathology was linked with insufficient sleep duration 1,2 (including sleep deprivation 3,4 ), poor sleep quality, 1,5,6 long latency, 7,8 low efficiency, 8,9 obstructive sleep apnea (OSA), 10‐12 excessive daytime sleepiness (EDS), 2,6 and fragmentation 8 . However, the generalizability and credibility of these findings are easily compromised by small sample size and heterogeneous definition of sleep problems.…”
Section: Introductionmentioning
confidence: 99%